Analisis Kepuasan Nasabah Produk Tabungan Terhadap Kualitas Layanan Customer Service Pada Bank bjb Kantor Cabang Pembantu Jember (Jurnal Kendali Akuntansi, 2024)
This study's goal is to understand consumer attitudes toward the services provided by customer service. This study is being conducted at Bank bjb Kantor Cabang Pembantu Jember. The method used in this study is a deskriptif kualitatif approach, while the data used in this study are obtained through a kajian kepustakaan approach by utilizing books, articles, or other written materials related to the study. The initial data for this study was obtained from observations and interviews with national banks that have one tabungan product, Bank bjb KCP Jember. The analysis's findings highlight the importance of customer service in improving the company's offerings in order to gain positive feedback and an increasingly successful business. Thus, Bank BJB KCP Jember can continuously strengthen its position in the banking industry.